Does banks size distort market prices? Evidence for too-big-to-fail in the CDS market - Manja Völz; Michael Wedow (Deutsche Bundesbank, 2009)
This paper examines the potential distortion of prices in the CDS market caused by too-big-to-fail. Overall, we find evidence for market discipline in the CDS market. However, CDS prices are distorted due to a size effect which arises when investors expect a public bail-out as a result of too-big-to-fail. A one percentage point increase in size reduces the CDS spread of a bank by about two basis points. We further find that some banks have already reached a size that makes them too-big-to-be-rescued. While the price distortion for these banks decreases the existence of banks that are considered to be toobig-to-rescue raises important new issues for banking supervisors.
Keywords: G14; G21; G28; 330; Market Discipline; Too Big To Fail; Too Big to Rescue CDS Spreads; Bank; Betriebsgröße; Credit Default Swap; Kreditversicherung; Börsenkurs; Risikoprämie; Bankinsolvenz; Bankgarantie; Staatliche Einflussnahme; Welt